EFEKTIVITAS PENDIDIKAN GIZI MENGGUNAKAN MEDIA EDUTAINMENT CARD TERHADAP PENINGKATAN PENGETAHUAN TENTANG PEDOMAN GIZI SEIMBANG PADA SISWA SEKOLAH DASAR - Diana Mustikaningsih; J Supadi; Mohammad Jaelani; Sri Noor Mintarsih; Susi Tursilowati (Poltekkes Kemenkes Semarang, 2019)
Background: Indonesia is still faced with a triple burden of nutrition, such as malnutrition, stunting and overnutrition. According to UNICEF, one of the cause nutrition problems is the lack of knowledge about nutrition. The prevention of health problem starts at the early stage, namely the understanding of balance nutrition guideline in school-age children. New method need to be made to make it easier for students to arrest nutrition message, namely in the form of edutainment cards.Objective: To determine the effectiveness of nutrition education by using the edutainment card method on knowledge about balance nutrition guideline in elementary school.Research Methods: The type of research is Experimental with pre and post-control group design design. Sampling using random sampling technique to get 30 treatment samples and 30 control samples. Research was in SDN Palebon 02, conducted in Februari 2019. The data collected are sample identity dataand knowledge of balance nutrition guideline. The data was analysed by independent t-test with 95% confidence level.Results: There was significant difference in knowledge about balance nutrition guideline in the treatment and control groups after intervention with edutainment card method (p value = 0.001).Conclusion: Edutainment card as a media for education is effective for increasing nutrition knowledge in children